The Role of Endocrine G Protein-Coupled Receptors in Ovarian Cancer Progression - Zhang, Qingyu; Madden, Nadine Ellen; Wong, Alice Sze Tsai; Chow, Billy Kwok Chong; Lee, Leo Tsz On (Frontiers in Endocrinology, 2017)
Ovarian cancer is the seventh most common cancer in women and the most lethal gynecological cancer, causing over 151,000 deaths worldwide each year. Dysregulated production of endocrine hormones, known to have pluripotent effects on cell function through the activation of receptor signaling pathways, is believed to be a high-risk factor for ovarian cancer. An increasing body of evidence suggests that endocrine G protein-coupled receptors (GPCRs) are involved in the progression and metastasis of ovarian neoplasms. GPCRs are attractive drug targets because their activities are regulated by more than 25% of all drugs approved by the Food and Drug Administration. Therefore, understanding the role of endocrine GPCRs during ovarian cancer progression and metastasis will allow for the development of novel strategies to design effective chemotherapeutic drugs against malignant ovarian tumors. In this review, we address the signaling pathways and functional roles of several key endocrine GPCRs that are related to the cause, progression, and metastasis of ovarian cancer.